Reputation, Governance And Competitive Advantage On Financial Performance Of Infaq: The Case Of Private Islamic Schools - Berahim @ Ab Rahman, Azira Hanani (2020)
The main financial resources of these Islamic private schools are student fees, but the fees alone are insufficient to cover the overall cost of the planned operation and development. As such, Islamic private schools in Malaysia rely heavily on infaq from individuals and corporate bodies. The purpose of this study was to explore the factors of reputation, governance and competitive advantage in influencing the sufficiency of infaq received among Islamic private schools in Malaysia. The conceptual framework for this study was developed from Resource Base Theory and Stakeholder Theory